The Effect of Pulmonary Hypertension on Renal Function Dynamics in Left-Heart Failure Patients - Robert Dragu; Adrian Abramovici; Kasem Abu Zeid (Biomedicines)
Objectives: Cardiorenal syndrome (CRS) is a complex disorder characterized by concurrent dysfunction of the heart and kidneys, with their detrimental effects perpetuating a bidirectional cycle. This study aimed to examine the clinical and hemodynamic factors associated with changes in renal function in patients with pulmonary hypertension (PH) secondary to chronic heart failure (HF). Methods: A total of 108 patients with HF were evaluated using right-heart catheterization. Results: 75 patients (69.4%) were diagnosed with PH. The mean baseline estimated GFR (beGFR) was similar in noPH (64 ± 21 mL/min/1.73 m2) and PH group (63 ± 23 mL/min/1.73 m2) (p = 0.71). After a median follow-up of 7 months, the last eGFR (leGFR) in the noPH and PH groups was comparable (49 ± 24 vs. 52 ± 25 mL/min/1.73 m2 respectively; p = 0.62). However, in the PH group, for patients with baseline Cr (bCr) < 1.5 mg/dL, the reduction in eGFR showed a graded inverse relationship to serum creatinine, as compared with bCr ≥ 1.5 mg/dL, for whom beGFR and leGFR demonstrated large overlap. In a multivariable regression analysis, the primary independent predictors of leGFR were baseline creatinine, age, diabetes mellitus, left ventricular ejection fraction below 45%, and use of mineralocorticoids antagonists. The model explained 66% of the variance in leGFR. Conclusions: In a cohort of left HF and PH, an inverse non-linear and graded association between the baseline serum creatinine levels and the variation in estimated GFR was demonstrated, contrary to those without PH, for whom this relationship was linear and constant. The distinct patterns of GFR decline influenced by age, low ejection fraction, diabetes, and mineralocorticoid underscore the need for individualized treatment strategies.